2021
DOI: 10.1038/s41380-021-01160-8
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids protect against inflammation through production of LOX and CYP450 lipid mediators: relevance for major depression and for human hippocampal neurogenesis

Abstract: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) can exert antidepressant, anti-inflammatory and neuroprotective properties, but the exact molecular mechanism underlying their effects is still not fully understood. We conducted both in vitro and clinical investigations to test which EPA or DHA metabolites are involved in these anti-inflammatory, neuroprotective and antidepressant effects. In vitro, we used the human hippocampal progenitor cell line HPC0A07/03C, and pre-treated cells with either EPA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 61 publications
4
43
0
Order By: Relevance
“…In contrast, cluster headaches, which are uncommon in ME/CFS and GWI, may be interpreted as exteroceptive pain with the arousal of sympathetic fight-flight reactions, motor agitation, and restlessness. The molecular mechanisms of sickness behaviors are complex but may involve IL6, IL1-beta, INF-alpha, and other cytokines as well as modulation of arachidonic acid cytochrome P450 metabolites and phosphatidylinositol derivatives by eicosapentaenoic acid (EPA) and effects on cannabinoid CB2 receptors [ 135 , 136 , 137 , 138 ]. EPA may have some benefits for treating anxiety [ 139 ] and PTSD [ 140 , 141 ] but has small non-clinical effects compared to placebo in depression [ 142 ].…”
Section: Dysfunction In Me/cfs and Gwimentioning
confidence: 99%
“…In contrast, cluster headaches, which are uncommon in ME/CFS and GWI, may be interpreted as exteroceptive pain with the arousal of sympathetic fight-flight reactions, motor agitation, and restlessness. The molecular mechanisms of sickness behaviors are complex but may involve IL6, IL1-beta, INF-alpha, and other cytokines as well as modulation of arachidonic acid cytochrome P450 metabolites and phosphatidylinositol derivatives by eicosapentaenoic acid (EPA) and effects on cannabinoid CB2 receptors [ 135 , 136 , 137 , 138 ]. EPA may have some benefits for treating anxiety [ 139 ] and PTSD [ 140 , 141 ] but has small non-clinical effects compared to placebo in depression [ 142 ].…”
Section: Dysfunction In Me/cfs and Gwimentioning
confidence: 99%
“…Perturbations in the CYP450-sEH pathway have now been reported in clinical studies of seasonal depression [ 80 ], major depression without T2DM [ 81 ], and major depression with T2DM [ 82 ]. A recent study found increased plasma levels of 17(18)-EpETE and 19(20)EpDPE in depressed patients receiving EPA or DHA supplementation, where higher epoxide levels were correlated with lower depression severity, suggesting that the benefits of omega-3 supplementation may depend on metabolism into neuroprotective mediators [ 81 ].…”
Section: Oxylipins and Complications Of Diabetesmentioning
confidence: 99%
“…Perturbations in the CYP450-sEH pathway have now been reported in clinical studies of seasonal depression [ 80 ], major depression without T2DM [ 81 ], and major depression with T2DM [ 82 ]. A recent study found increased plasma levels of 17(18)-EpETE and 19(20)EpDPE in depressed patients receiving EPA or DHA supplementation, where higher epoxide levels were correlated with lower depression severity, suggesting that the benefits of omega-3 supplementation may depend on metabolism into neuroprotective mediators [ 81 ]. In human hippocampal cells, co-treatment with EPA and DHA prevented cytokine-induced reduction in neurogenesis and apoptosis via increases in EPA-derived 17(18)-EpETE (17,18-Epoxy-5,8,11,14-eicosatetraenoic acid) and DHA-derived 19(20)EpDPE levels, an effect that was further enhanced with the addition of an sEH inhibitor [ 81 ].…”
Section: Oxylipins and Complications Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor, combined with agricultural practices driven toward corn production and a dietary preference toward processed foods, shifted fatty acid composition in the modern Western diet from saturated and monounsaturated to increasing concentrations of polyunsaturated fatty acids (PUFAs), specifically omega-6 linoleic acid (LA, 18:2), resulting in a corresponding increase in LA in human adipose composition since the 1950s ( 1 ). The metabolism of PUFAs results in numerous regulatory lipid mediators that influence inflammation and metabolism, and many observational studies have found associations between concentrations of parent PUFAs, their metabolites, and numerous diseases ( 2 , 3 ). For example, higher dietary intake of omega-3 fatty acids found predominantly in cold-water fish is associated with better health outcomes and antiinflammatory properties ( 4 ), while the omega-6 fatty acids and their metabolites are associated with more complex phenotypes.…”
mentioning
confidence: 99%